Fasciitis Complicating Subcutaneous Injection of Interferon Beta - Curtis L Cooper; Rachel Gerstein; Kelly Kaita (Canadian Journal of Gastroenterology)
Data pertaining to 65 patients treated at the Health Sciences Center Hepatology Research Unit in Winnipeg, Manitoba describing local complications related to subcutaneous interferon (IFN) injection administered to treat hepatitis C virus infection are presented. Nine patients experienced local erythematous reactions at the injection region. No life-threatening complications were identified. One case of fasciitis complicating IFN injection – a complication not previously reported – was successfully managed with surgical debridement and antibiotic therapy. This case is a dramatic example of why sterile technique during infections must be adhered to.